2010
DOI: 10.1371/journal.pone.0010262
|View full text |Cite
|
Sign up to set email alerts
|

Fast Mapping of Global Protein Folding States by Multivariate NMR: A GPS for Proteins

Abstract: To obtain insight into the functions of proteins and their specific roles, it is important to establish efficient procedures for exploring the states that encapsulate their conformational space. Global Protein folding State mapping by multivariate NMR (GPS NMR) is a powerful high-throughput method that provides such an overview. GPS NMR exploits the unique ability of NMR to simultaneously record signals from individual hydrogen atoms in complex macromolecular systems and of multivariate analysis to describe sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…Although it has been reported that low concentrations of SDS can induce cooperative conformational transitions, 7,28 this data shows that the effect of dodine is fundamentally different from the effect of its two constituent parts at the same concentration.…”
Section: Resultscontrasting
confidence: 57%
“…Although it has been reported that low concentrations of SDS can induce cooperative conformational transitions, 7,28 this data shows that the effect of dodine is fundamentally different from the effect of its two constituent parts at the same concentration.…”
Section: Resultscontrasting
confidence: 57%
“…A weakness with the chromatographic approach is that the method does not allow us to control the protein-lipid ratio and, indeed, it often leads to complexes with highly variable stoichiometries [7,[30][31][32]37]. Initial efforts to produce HAMLET complexes by other approaches such as simple mixing under different solvent conditions were not successful [2,33,38].…”
Section: Preparation Of Cytotoxic A-la:oa Complexes By Different Apprmentioning
confidence: 99%
“…S6). A small cooperative transition in the signal with C m = 0.08 m M is followed by a gradual loss of structure as a linear function of SDS concentration.…”
Section: Resultsmentioning
confidence: 97%